The crystal structure of (E)-1,2-bis(benzo[e][1,2]azaborinin-2(1H)-yl)ethene, C18H16B2N2 - Zhou, Jing (Zeitschrift für Kristallographie. New crystal structures, 2024)
, monoclinic, 2/ (no. 15), = 34.048(12) Å, = 5.720(2) Å, = 7.666(3) Å, = 96.803°, = 1482.5(9) Å , = 4, ) = 0.0412, ) = 0.1152, T = 150 K.